ANALISIS TINGKAT KONDISI FISIK ATLET SEPAK TAKRAW SPOBDA GORONTALO - Raflin Pakili; Hartono Hadjarati; Meri Haryani; I Kadek Suardika; Edy Dharma Putra Duhe (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the physical condition of SPOBDA Gorontalo sepak takraw athletes. The research method used is quantitative descriptive. Based on the data descriptions and analysis results from 9 physical conditions, the athlete's strength falls into the good category, flexibility is in the moderate category, explosive power is good, endurance is good, balance is moderate, coordination is very good, accuracy is moderate, agility is moderate, and speed is good. And they achieved an average score of 45.6, indicating that the athletes' physical condition is still classified as Good. This, of course, affects the players' performance in sepak takraw, such as getting tired easily, lacking agility during games, and also weakening their service, smash, and feeder power during play. These results show that most athletes already have adequate physical abilities, though some deficiencies can still be found in certain areas. High performance in some athletes also indicates that the training conducted by the coaches is quite effective, although it still needs to be improved more evenly. The solution that athletes should do is to focus more on physical conditioning training because it is very good for athletes to avoid the risk of injury, and for coaches, it's better to design a more structured training program, improve techniques, boost motivation, conduct regular evaluations, and maintain the athletes' fitness and recovery so that their physical abilities develop to the fullest.